2013
DOI: 10.1007/s11273-013-9319-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mechanism for the reduction in soil water in poplar (Populus deltoides) plantations in Dongting Lake wetlands

Abstract: The use of large-scale tree plantations has provoked increasing concern regarding the negative effects on local environments in different ecosystems. However, the physiological mechanism underlying the reduction in soil water by tree plantations in wetlands is not clear. The aims of this study were to investigate the effects of poplar (Populus deltoides) plantations on soil water content and to elucidate the underlying physiological mechanisms. To this end, we conducted a 1-year fixed-plot investigation of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In wetland ecosystems, studies have shown that elevation had a strong influence on understory vegetation due to the hydrological conditions such as soil moisture and water level fluctuations14. In monitored plots at the same elevation, the mean soil water content was lower in poplar areas (23.5%) versus in the reedy areas (31.3%), presumably due to higher transpiration capacity in the poplars17. Excessive loss of soil water might have changed wetlands to dry lands and resulted in a lower ratio of hygrophytes, but a higher ratio of mesophytes or xerophytes, in the poplar areas compared to that in the reed areas.…”
Section: Discussionmentioning
confidence: 99%
“…In wetland ecosystems, studies have shown that elevation had a strong influence on understory vegetation due to the hydrological conditions such as soil moisture and water level fluctuations14. In monitored plots at the same elevation, the mean soil water content was lower in poplar areas (23.5%) versus in the reedy areas (31.3%), presumably due to higher transpiration capacity in the poplars17. Excessive loss of soil water might have changed wetlands to dry lands and resulted in a lower ratio of hygrophytes, but a higher ratio of mesophytes or xerophytes, in the poplar areas compared to that in the reed areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sap flow characteristics vary with species and growth status, as well as with meteorological, environmental, and edaphic features (Brito et al, 2015;Du et al, 2011). In areas with insufficient water, for example, soil water conditions can restrict many physiological processes (Li et al, 2014b). Plants in these areas tend to deepen and extend their root systems to exploit substantial quantities of soil water for transpiration (Chen et al, 2014c;Limousin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The average annual temperature is 16.2-17.8°C. Temperature is highest in July and lowest in January, and the region has a frost-free period of 259-277 days per year [21].…”
Section: Study Areamentioning
confidence: 99%